Choose France! Containment, circulation and postcolonial (dis)continuities in transnational education - Alice Bobée; Jana Maria Kleibert (Globalisation, Societies and Education, 2022)
Understanding the post-colonial geographies of transnational education spanning France and Africa requires a closer look at the actors that facilitate and inhibit international student mobilities: transnational higher education institutions. Conceptualising offshore campuses as infrastructures of selective (im)mobility, we analyse how French business and engineering schools shifted their strategies from envisioning their campuses in Francophone Africa as `alternatives to migration' towards facilitating various circulations. We show how French offshore campuses do not simply enact French migration and higher education policies but increasingly adapt to competitive pressures and demands of fee-paying students for mobility, thereby emulating `Anglo-Saxon' market-oriented strategies.
Keywords: 320; International branch campuses; transnational education; post-colonialism; international student mobilities; migration; France